Influence of Trigonella foenum graecum seed extract as root canal irrigation agent on root surfaces: A scanning electron microscope/energy dispersive X‐ray analysis study. Issue 12 (24th August 2019) - Tosun, Samet; Karataslioglu, Emrah
Abstract: The purpose of this in vitro study was to investigate the effect of Trigonella foenum graecum seed extract (TFGSE) as a root canal irrigation agent on the surface of instrumented root canals and on changes in the mineral contents of the root dentin. A total of 90 extracted human mature maxillary central incisor teeth with a single root and without root resorption were selected. The specimens were subdivided into five groups according to irrigation protocol groups G0: distilled water ( n = 15): G1: Sodium hypochlorite (5.25% NaOCl); G2: 1% TFGSE G3: NaOCl +17% EDTA (3 min); G4: NaOCl+1% TFGSE; G5: 1% TFGSE +17% EDTA. All the roots were sectioned longitudinally into two halves and examined under scanning electron microscope/energy dispersive X‐ray analysis (SEM/EDX) to assess changes in the mineral content of the tooth. Smear layer removal from root canals was evaluated with scanning electron microscopy (SEM). A statistical analysis was performed using the Kruskal–Wallis test. The most effective irrigation protocols in removing smear layer occurred with TFGSE and NaOCl, both with rinsing with 17% EDTA. TFGSE was more effective than NaOCl for removing the smear layer. The results showed the ability of 1% TFGSE to remove the smear layer from the root canals. TFGSE is a promising alternative irrigation agent for root canals. Abstract : The study revealed a reduced smear layer on the surface of root canals treated with TFGSE. TFGSE+ EDTA is as effective as NaOCl+ EDTA in smear layer removal When TFGSE was used as an irrigation agent, there was no significant change in the mineral contents of the root dentin for the Ca, P, C, Na, Mg, and Ca/P ratio.